Investigation into the coupled 1D and 3D numerical modeling of an air-cooled heat exchanger configuration - Koekemoer, O.C. (North-West University, 2018)
One dimensional (1-D) systems CFD can be used to simplify the analyses of thermal-fluid problems with complex geometries as it has the capability to provide quick solutions on fluid dynamics such as pressure changes, temperature fluctuations and flow rates. Three-dimensional (3-D) component CFD is generally used to model more complex geometries, due to its ability to provide detailed information on fluid dynamics whether it be flow regimes, chemical reactions or multiple phase changes. Existing analytical models and experimental methods for the analysis of Air-Cooled Heat Exchangers (ACHE) are limited in their applicability and a full 3-D CFD analysis thereof can be very resource intensive. This study proposes the use of a coupled 1-D/3-D modelling approach to address these issues. The coupled 1-D/3-D modelling approach, utilizing Ansys® Fluent and Flownex® SE, was used to set up different air-cooled heat exchanger test configurations which were then compared with equivalent full 3-D CFD models simulated using Star-CCM+. The coupling procedure, between Flownex and Ansys Fluent was achieved through the continuous exchange of flow boundary conditions to ensure mass, momentum and energy was conserved through the single combined flow domain. The Flownex and Fluent networks are explicitly coupled by transferring temperature and heat flux between the two networks. For all the ACHE configuration test cases, the temperature of the water exiting the pipe network, the number of iterations, solution time and model size are the main attributes examined. These results will be compared with the relevant verification test case having the same input specifications and set up. This comparison of results between the two different solution approaches will form the basis on which the coupled 1-D/3-D modelling approach is tested.
MEng (Mechanical Engineering), North-West University, Potchefstroom Campus
Keywords: Air-Cooled Heat exchangers; one dimensional1-D; three dimensional; 3-D; coupled 1-D/3-D modelling; Computational Fluid Dynamics; CFD; duct flow; Numerical modelling